2014
DOI: 10.1016/j.jnucmat.2014.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature on surface modification of W exposed to He particles

Abstract: The effect of combined heating and helium particle flux on annealed tungsten samples has been studied in the neutral beam facility GLADIS. He beams with power densities of 2.4 MW/m 2 and 9.5 MW/m 2 were used to adiabatically load the samples to peak surface temperatures from ~ 950 °C (1223 K) to ~ 2700 °C (2973 K). Changes in the surface morphology resulting from combined heat and the flux exposure were studied for He fluences up to 3×10 22 /m 2 . Typical structures for the sample loaded at ~ 950 °C (1223 K) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…After He loading at a peak surface temperature of 900 °C with a fluence of 1 × 10 22 m -2 , a large number of blisters are observed on the exposed surface, as shown in Figure 3. Blistering on W is widely reported in previous study [17][18][19]. Blistering on the W-5V shows some differences due to the three typical phase regions.…”
Section: Surface Modification After He Loading At a Peak Surface Tempmentioning
confidence: 71%
“…After He loading at a peak surface temperature of 900 °C with a fluence of 1 × 10 22 m -2 , a large number of blisters are observed on the exposed surface, as shown in Figure 3. Blistering on W is widely reported in previous study [17][18][19]. Blistering on the W-5V shows some differences due to the three typical phase regions.…”
Section: Surface Modification After He Loading At a Peak Surface Tempmentioning
confidence: 71%
“…The changes in W surface microstructures under high-flux He + irradiation have been described previously [12,18,19]. The surface damage processes are diffusion-controlled, and strongly influenced by surface temperature [19]. Under a rather high surface temperature (>1000 K) condition, He nanobubbles rapidly grow by thermally migrating and coalescing with each other, and push up the surface, leading to the formation of nano-fuzzes [18].…”
Section: Discussionmentioning
confidence: 86%
“…The changes in W surface microstructures under high-flux He + irradiation have been described previously [12,18,19]. The surface damage processes are diffusion-controlled, and strongly influenced by surface temperature [19].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…It has been indicated that the functional properties and structure performance of W in terms of particle irradiation resistance [8][9][10][11][12][13][14][15][16][17], surface morphology after irradiation [18][19][20][21], thermal conductivity [22] and fracture toughness [23] were related to its crystal orientation. Specifically, W grains with low crystallographic index displayed better irradiation resistance under deuterium plasma [8], helium neutral beam [9], helium/ hydrogen ions [10] and Ga + ion [11].…”
Section: Introductionmentioning
confidence: 99%